Meningkatkan Kinerja SDM Melalui Learning Organization dan Komitmen Organisasi - Anisah (Haka Vyza Media, 2026)
This study aims to analyze the effect of learning organization on employee performance with organizational commitment as a mediating variable. This research employs a quantitative approach with an explanatory design. The population consists of banking employees in Jambi City, with a sample of 80 respondents selected using purposive sampling based on a minimum of four years of work experience. Data were collected through questionnaires using a Likert scale. The data analysis technique used Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with SmartPLS software. The results indicate that learning organization has a positive and significant effect on both employee performance and organizational commitment. Organizational commitment also has a positive and significant effect on employee performance. Furthermore, organizational commitment mediates the relationship between learning organizationand employee performance. These findings suggest that the effective implementation of a learning organization can improve employee performance both directly and indirectly through enhanced organizational commitment